Changes of the abundances of Fe, Ni, Zr isotopes due to neutron radiative capture reactions in heavy water reactors. (June 2020) - Cui, Zengqi; Bai, Huaiyong; Jiang, Haoyu; Lu, Yi; Chen, Jinxiang; Zhang, Guohui
Abstract: The abundances of the nuclides in nuclear materials change over time in reactors because of neutron-induced reactions like ( n, γ ), ( n, α ), ( n, p ), etc. Among them, the effect caused by ( n, γ ) reactions is especially significant in heavy water reactors because they have a large proportion of thermal neutron flux, and the cross sections of ( n, γ ) reactions for most nuclides are dominant in the thermal region than in regions of higher energies. The changes of the abundances of Fe, Ni, and Zr isotopes in CANDU-6 reactors over 25 years through radiative capture reactions (thermal neutron flux of 2.7 × 10 18 n·m −2 ·s −1, and effects of epithermal, resonance, and fast neutrons are also included) are calculated. Results show that for Fe and Ni isotopes, the changes of abundances are obvious: 57 Fe enriches from 2.12% to 12.22%; 58 Ni drops from 68.09% to 36.88% and 60 Ni increases from 26.23% to 44.35%. For Zr isotopes, the effect is also noticeable, with the abundance of 90 Zr and 91 Zr decreasing from 51.45% and 11.22% to 50.67% and 9.58%, respectively. . Present results are verified with the ALARA code. Based on these calculations, a new approach to estimating the neutron fluence in heavy water reactors is proposed according to the abundances of several stable isotopes including 56 Fe, 57 Fe, 58 Ni and 60 Ni. Highlights: The abundance change effect for Fe, Ni, and Zr in CANDU-6 reactors is calculated. Present results are compared and verified with ALARA code. An approach to estimating the neutron fluence in heavy water reactors is proposed.